Misyar Marriage and Women’s Autonomy in Muslim Countries: A Maqashid al-Usrah Perspective - Nasiri, Nasiri; Istifhama, Lia; Malaka, Zuman; Achmad, Achmad; Zahroh, Lailatu (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2026)
Misyar marriage remains a contested form of marital arrangement in contemporary Muslim societies because it allows spouses to negotiate or waive certain marital obligations, including co-residence, financial support, and public visibility. This study examines how misyar marriage is practiced by women from relatively privileged socio-economic backgrounds in Saudi Arabia, Morocco, Egypt, Malaysia, and Indonesia, and evaluates these practices through the lens of gender analysis and Jamaluddin Athiyyah’s maqasid al-usrah. The study employs a qualitative multi-site design using in-depth phenomenological interviews, field observations, and document analysis. Data were collected from 20 informants across the five research settings. The findings show that misyar practices vary across contexts but commonly involve motives related to marital flexibility, negotiated domestic autonomy, ease of exit, companionship, sexual and emotional needs, and lineage aspirations. For some women, misyar functions as a strategy for exercising agency in negotiating intimate relationships outside conventional marital expectations. At the same time, recurrent secrecy, weak institutional recognition, unstable obligations, and limited legal protection generate gendered vulnerabilities, particularly in relation to marital security, family continuity, and economic rights. Viewed through Athiyyah’s maqasid al-usrah, the practices documented in this study do not produce a uniform outcome, but they repeatedly reveal difficulties in fulfilling the broader ethical and institutional objectives of family life in a stable and sustainable manner. This study contributes to debates on Islamic family law by connecting women’s lived experiences, cross-national variation, and maqasid-based family ethics.Keywords: Misyar marriage; maqasid al-usrah; women’s autonomy.